Performance Evaluation of SIP Server under Virtualization Environment Along with the Most Common Security Threats - Kolhar, Manjur; M Abualhaj, Mosleh; Alameen, Abdullah (Bulletin of Electrical Engineering and Informatics, 2016)
Virtualization is the central point which empowers cloud infrastructure. Many services such as Web-based applications, databases and instant messaging servers have been running on virtual systems to reduce total cost ownership and to get immediate returns on investments. However, applications which are concerned with the latency, such as Voice over IP (VoIP) applications, are rarely found in virtual systems. Hence, our aim is to study VoIPâs behavior in the virtualization environment. Apart from this, VoIP infrastructure should also be equipped with a security shield to protect itself from various forms of security threats; this security setup also brings an extra overhead response time. Hence, in this article, we have implemented VoIP on virtual machine (VM-VoIP) and measured the signaling process of VoIP systems. Performance of the proposed system is studied with and without a security shield.Â  It is observed that the virtualization environment never induces delay during the registration request delay (RRD) part of the signaling. However, the analysis shows that the delay increases with the number of calls during the session request delay (SRD) part of signaling. In addition, the VM-VoIP system consumes more CPU for VoIP call sessions under the security shield.